TOWARDS MULTIPLE DISCIPLINARITY IN RESEARCH AND PRACTICE - Lehtinen, Uolevi (European Scientific Journal, ESJ, 2015)
The purpose of this article is to describe the possibilities to strive for multiple disciplinarity in research and practice. First, multiple disciplinarity and its methods i.e. blending, borrowing and combining are examined. A new concept of multiple modelling is introduced in this connection. Some empirical studies that illustrate the idea and rationale of combining, borrowing and blending as methods of multiple disciplinarity and modelling in business administration are then depicted. The empirical results based on the author’s four studies and three secondary studies show that there are some gaps between marketing practice and current theories. The results also confirm that there is a significant multidisciplinary (parallel) use of both approaches, often some kind of use of the combinations of the approaches and a strong need to find out how to combine the approaches properly. The possibilities of borrowing and blending as methods toward multiple disciplinarity and modelling are also discussed. Finally, there is a discussion about the nature and reasons of multiple disciplinarity and modelling. Some challenges to marketing researchers, educators and managers are presented. Also some generalizations and additional challenges concerning the total utilization possibilities of multiple disciplinarity are raised.